A Methods engineering study on Universal Stainless Ware Manufacturing Company, Inc - Baradas, Jennifer; Dela Fuente, Janelle; Santos, Gari Lenard (Diliman, Quezon City College of Engineering, 2001)
Universal Stainless Ware Manufacturing, Inc has been chosen as the site for the study. US Wares carries a wide variety of high quality stainless products. Due to time constraints, the group decided to focus onthe production of only one product, the CSPT 20. CSPT 20 is part of two sets, the Crown 7 pcs Set (C-7) and the Economic Crown 7 pcs-Set. According to the Vice President, C-7 comprises majority of their market share. The group conducted plant visits and interviewed the workers and management to gather information. The group conducted further discussions that led to the identification of problems that needed attention. Based on the analysis conducted by the group, the following core problems have been identified : carelessness of workers, no regular maintenance of the machines, lack of materials handling equipment and inefficient layout. Through brainstorming, the group was able to come up with alternatives to the problems stated. Using Potential Problems Analysis, these alternatives were evaluated to come up with the best possible solution. For the problem on careless of workers, the group suggests that a reward system be implemented. In the reward system, the ratio of rejects to total output of the worker will be computed at the end of each day and averaged at the end of the month. The worker who has the lowest averaged ratio will be given a bonus at the end of the month. The group thinks that this will motivate the workers to pay more attention to their jobs. The estimated cost for his suggestion is PhP336.00 per month. Implementation period will start at the end of the month when the management will inform the workers about the reward system. Recording the ratio of rework to total output will start at the beginning of the next month. A reward of PhP250.00 will be given to the deserving worker at the end of each month. For the problem regarding machine maintenance, the group suggests that the company hire the services of a machine maintenance company. The machine maintenance company will determine the schedule of maintenance. For the problem on materials handling equipment, the group suggests the use of plastic crates. These plastic crates will be suspended from the ceiling by pulleys and used to transport products from the second floor to the first floor. The total estimated cost for this plan is PhP2192.50. Implementation period will start next month with the setting up of the crates and the pulleys. For the problems regarding layout, the group suggests the product layout. Setting up for this layout will be simpler and will require less set-up time than the other suggestion, which was to convert to a cellular manufacturing layout. The total cost for this plan is PhP3250.00. This plan will be implemented before the start of production of the new batch. The group also conducted a time study. From the time study, the group obtained time standards that were very different from the ones currently applied. The group presented a table comparing the current time standards to the obtained time standards and suggested a new quota. At the end of the study, the group suggested areas for further study such as a quality control study and comprehensive methods engineering of the company.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis